Flood Hazard Assessment in Phu Loc District, Thua Thien Hue Province in the Context of Climate Change - Kim Ngoc Anh, Nguyen; Hong Thuy, Nguyen; Bach Tung, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2021)
The paper presents a number of results of flooding depth assessment in Phu Loc district, Thua Thien Hue province according to separate causes in case of climate change. The risk of flooding in Phu Loc is determined by 3 causes: Rivers at high stages can inundate the unprotected upstream part of the area and overflow the River dikes (fluvial flood), Heavy rainfall which cannot be effectively drained can cause inundation (pluvial flood) and Strong storms at sea occurring at high tide can raise water levels by several meters and overflow the sea dike (coastal flooding). Based on these three causes, the study evaluates the risk of flooding for separate causes with return periods of 10, 30, and 100 years in combination with climate change scenarios (MONRE, 2016). Sea level rise and rainfall and flow are expected to increase in 2030 and 2070. Mike Flood model is used as a scenarios calculation tool after calibrating and validating model parameters with Nash - Sutcliffe indicators at Kim Long and Phuc Oc stations achieved quite good results (0,95; 0,96; 0,86 and 0,70) and compared flooded area with satellite images. The impact of these three flood risks on Phu Loc is almost the same, with the overall flooding area increasing due to climate change with an increase of 1% to 5%.